Chapter 12 Individual Work Pricing by Non-fungible Personal Tokens ("NFT Gig Tokens") - a New Opportunity for Gig Workers - Marchewka-Bartkowiak, Kamilla (Routledge Studies in Labour Economics, 2023)
The COVID-19 pandemic transformed the way people operate in all fields of their activity - individual, social, economic, cultural, civic, to name the most essential spheres. One of the crucial changes to the rules existing within pre-pandemic societies was the modification of the work environment and principles (Ralph et al., 2020; Masood et al., 2022). The patterns developed within the gig economy, which are based on the idea of flexibility and the use of technological communication platforms, proved to be the most common response to the change (Diab- Bahman & Al-Enzi, 2020). When it comes to specific problems that were highlighted by the pandemic, the issue of labour pricing occurred to be of concern. The development of online communication tools created new opportunities to provide services and share results of one's work via the Internet. It is worth noting that even before the COVID-19, the issue of work valuation was crucial for some groups, for example, for artists. The token became an important way of work monetisation both for them and the new services providers. More and more one hears about artists converting their artworks (the results of their work) into non-fungible tokens (NFT tokens). But will only celebrities (artists, actors, and influencers) use this tool in the future? This question occurred to be an extremely relevant matter in a (post)pandemic world. It seems that NFT gig tokens are an answer to the challenges occurring on the labour market, related to the popularisation of the employment model in the gig economy and the issue of valuing work offered by gig workers.